Corruption Prevention Assistance Through Structural Adaptation and Local Parenting Culture in Sendang Village, Wonogiri - Setiyawan, Wahyu Beny Mukti; Sumarto, Slamet; Abdilah, Yan Amal; Khunaefi, Muhammad Wildan; Angkoso, Yulius Willy Ciptadi (Universitas Negeri Semarang, 2024)
This initiative aims to enhance corruption prevention in Sendang Village, Wonogiri Regency, through an innovative parenting education approach. It focuses on developing and distributing e-comics as tools to instill values of transparency and accountability among residents, including children. The program was implemented in five stages: (1) Situational Analysis and Needs Assessment, (2) Development of E-Comic-Based Educational Materials, (3) Training and Dissemination of E-Comics to Village Officials and Residents, (4) Community Empowerment through Discussions and Anti-Corruption Campaigns, and (5) Evaluation and Documentation of Outcomes. The results demonstrated a significant increase in public awareness of corruption and the community's role in safeguarding village fund management. The e-comics effectively engaged diverse audiences by simplifying complex issues, while training and discussions empowered the community, fostering accountability and collective action. This initiative highlights the effectiveness of integrating innovative educational tools with local cultural values, offering a replicable model for rural communities in Indonesia. It contributes to the national anti-corruption movement by promoting transparency and grassroots engagement.